2002
DOI: 10.1046/j.1365-2044.2002.02601.x
|View full text |Cite
|
Sign up to set email alerts
|

Safer epidural and spinal connectors*

Abstract: SummaryInadvertent cross-connection of epidural local anaesthetic delivery systems with intravenous lines can cause significant morbidity and even death. Inadvertent intrathecal injection of toxic intravenous drugs has already led to many deaths. If epidural and spinal systems had the standard Luer lock connection reversed the problem would be prevented. The practical implications of this idea are explored. Patient safety would be enhanced if this system were adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Although the triggering event had numerous contributory procedural weaknesses, initial investigative reports promoted a technical solution in the form of non-Luercompatible connectors for neuraxial interventions [24]. These proposals have been endorsed by key international figures in the field of patient safety [4] and individual members of the UK anaesthetic community [21,25,26], and have prompted published design solutions in Canada [27] and the UK [28]. …”
Section: Uk Strategymentioning
confidence: 99%
“…Although the triggering event had numerous contributory procedural weaknesses, initial investigative reports promoted a technical solution in the form of non-Luercompatible connectors for neuraxial interventions [24]. These proposals have been endorsed by key international figures in the field of patient safety [4] and individual members of the UK anaesthetic community [21,25,26], and have prompted published design solutions in Canada [27] and the UK [28]. …”
Section: Uk Strategymentioning
confidence: 99%
“…Whilst the nuclear engineers had 3 hours to deal with a potential disaster, anaesthetists must diagnose the problem in 3 minutes. Failure to check the equipment (its patency and correct position) when the patient does not respond to treatment of a 'problem airway' features time and time again in anaesthetic disasters [2,3]. This first principle is already known, and so is the warning sign: the combination of hypoxaemia and bradycardia.…”
mentioning
confidence: 99%
“…We agree with Dr Powell that patients should not present for vascular surgery without appropriate pre-operative preparation. However, although it is suggested that all patients presenting for vascular surgery should be considered for statin therapy [1], only half of elective abdominal aortic aneurysm (AAA) surgery patients receive statins [2]. The cardiac outcome of major vascular surgical patients may therefore be adversely affected by inadequate medical therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The disaster of repeated deaths due to this design fault has led to the recommendation that dedicated route-specific connectors be developed [2,3]. We describe the initial clinical evaluation of such a connector for the neuraxial route.…”
mentioning
confidence: 99%